UPAYA GURU BIMBINGAN DAN KONSELING MENGATASI PERILAKU PORNOGRAFI PADA SISWA DI SMP NEGERI 1 PALUPUH KABUPATEN AGAM - Esa Yusni Saputri; Dodi Pasila Putra; Deswalantri; Alfi Rahmi (Universitas Pahlawan Tuanku Tambusai, 2022)
The main problem in this study is a problem related to deviant behavior, namely student cellphones containing pornographic images and videos, known by the search history on their smartphones. They save pornographic video sites and view them when the teacher is not around. There are students who cannot limit their association with the opposite sex and so on. The purpose of this study was to find out what the guidance and counseling teacher's efforts were to overcome pornographic behavior in students at SMP Negeri 1 Palupuh, Agam Regency. This type of research is a field research (Field Research) with a qualitative descriptive method, namely research that produces descriptive data in the form of written or spoken words from people and observable behavior. Informants in this study were divided into two, namely key informants and supporting informants. The key informant is the guidance and counseling teacher, the supporting informant is six students. Data collection techniques used are observation, interviews and documentation. Based on the results of the study indicate that the efforts made by the guidance and counseling teachers to overcome pornographic behavior in students are using curative efforts. Curative effort is an activity or series of treatment activities to overcome a problem that occurs. In curative efforts there is an alleviation function where the alleviation function is an effort made to overcome problems through guidance and counseling services with the aim that deviant behavior does not occur again. Curative efforts are provided through basic services with individual counseling strategies, providing educational punishments to students and cooperating with related parties. Keyword: Guidance and Counseling Teacher Efforts, Pornographic Behavior